Evaluation of nutrient content and caloric density in commercially available foods formulated for senior cats. (10th July 2020) - Summers, Stacie C.; Stockman, Jonathan; Larsen, Jennifer A.; Sanchez Rodriguez, Anais; Zhang, Lei
Abstract: Background: Cat foods marketed for senior cats (≥7 years) are available to owners. The variability in the nutritional content of these foods is unknown. Objectives: To measure the caloric density and caloric distribution of crude protein, crude fiber, crude fat, phosphorus, calcium, magnesium, sodium, potassium, and vitamin D3 in commercially available foods for senior cats and to compare nutrient content with foods for adult cats. Samples: Thirty‐one senior and 59 adult commercial nontherapeutic cat food products. Methods: Descriptive study. Crude protein, crude fiber, and crude fat were measured using Dumas nitrogen combustion, Ankom filter bag technique, and acid hydrolysis, respectively. Mineral concentrations were measured using inductively coupled argon plasma‐optical emission spectroscopy. Vitamin D3 was determined by liquid chromatography with tandem mass spectrometry. Caloric density was calculated using modified Atwater values. Results: The evaluated nutrient concentrations in all foods for senior cats met the values of the Association of American Feed Control Officials Cat Food Nutrient Profile for adult maintenance. Foods for senior cats had significantly higher crude fiber content when compared to foods for adult cats ( P < .0001). No significant difference in crude protein, crude fat and mineral concentrations was found between foods for senior and adult cats. Conclusions and Clinical Importance: Foods marketed for senior cats are highly variable in their caloric density and nutrient content and, except for crude fiber, are similar to foods for adult cats. Veterinarians should avoid broad recommendations regarding commercially available foods for senior cats, and dietary recommendations should reflect the patient's individual needs.